Experiencing and responding to extreme weather: lessons from the Cook Islands. Issue 5 (4th May 2023) - Clissold, Rachel; McNamara, Karen E.; Westoby, Ross; Wichman, Vaine
ABSTRACT : Catastrophic extreme weather events are destructive, costly, and bring about significant harm and distress. As a consequence of a warming world, extreme weather is only expected to increase in intensity. Unravelling the ways that frontline communities, such as those in the Cook Islands, are experiencing, preparing for, responding to, and recovering from, extreme events over time is vital to document, learn from, and share widely. This paper, drawing from 10 interviews with local Cook Islanders from both urban and remote settings, explores people's perspectives and experiences of, as well as responses to, extreme weather events, with a focus on droughts and cyclones. We found that the immediate devastation of cyclones and the chronic devastation of droughts has impacted participants in diverse ways, most of which take an emotional toll and affect people's abilities to meet household needs. These participant experiences with extreme weather events and the subsequent lessons that have transpired have led to the development of significant local knowledge and traditional coping strategies which enable anticipation, preparation, and adaptation. We highlight the ways that participants draw on cosmology, worldviews, and community resources for different courses of action in response to extreme weather. Tacit knowledge and endogenous spiritual and community resources offer Cook Islanders agency, hope and resilience in the face of climate change into the future.